A cross-sectional study of cervical Papanicolaou smear changes in antenatal women - Gautam, Nikita; Devi, Rajkumari Praneshwari; Moirangthem, Priyadarshini; Vaishnav, Anmol (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Cervical cancer is a preventable malignancy characterized by a prolonged preinvasive phase that allows early detection. Despite effective screening tools, coverage in India remains inadequate. This study evaluates cervical cytological findings in pregnant women and highlights antenatal care as a valuable opportunity for opportunistic cervical cancer screening, especially in settings where routine screening coverage is low.” Methods: This hospital-based cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, RIMS Imphal. A total of 354 pregnant women fulfilling the inclusion criteria underwent Papanicolaou (Pap) smear screening. Cytological findings were reported according to the Bethesda system. Associations between Pap smear findings and variables were analysed using chi-square test. Results: Most participants were aged 21-30 years (72.4%) followed by 31-35 years (13%). Pap smear findings revealed negative for intraepithelial lesion or malignancy (NILM) in 76.8% of cases. Inflammatory smears were observed in 9.6%, bacterial vaginosis in 5.4%, unsatisfactory smears in 7.9%, and low-grade squamous intraepithelial lesion (LSIL) in 0.3%. A statistically significant association was observed between socio-economic status and Pap smear findings (p<0.01). No significant association was found with education level or age at marriage. Conclusions: The findings highlight that antenatal care provides an important opportunity for opportunistic cervical cancer screening. Incorporating Pap smear screening into routine antenatal services may improve early detection of cervical abnormalities and strengthen cervical cancer prevention strategies in low-resource settings.